Moral panics and social control in the COVID-19 pandemic
1 online resource (168 pages)
Keywords: Moral Panics and Social Control in the COVID-19 Pandemic presents a series of case studies which focus on particular social processes and interactions during the COVID-19 pandemic, applying the tools offered by classical studies on moral panic and moral panic theory to illuminate both political and popular responses.Each case study explores the emergence, development, and impact of forms of moral panic in response to the coronavirus outbreak. In doing so, each chapter addresses the intersectional impact of moral panics upon vulnerable and/or stigmatized groups and outlines how moral panics have informed policies, interventions, and social mechanisms introduced by governments. Incorporating case studies from across the globe and drawing upon approaches from different disciplines, the chapters in this volume offer a wide-ranging and multi-faceted analysis of the varying responses to the coronavirus outbreak.The book highlights aspects of interest for students and scholars in the social sciences, educators, policymakers, and practitioners with an interest in moral panics, responses to the COVID-19 pandemic, and mechanisms of social control.